2006
DOI: 10.1044/1092-4388(2006/021)
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Augmentative and Alternative Communication Intervention on the Speech Production of Individuals With Developmental Disabilities: A Research Review

Abstract: Future research is needed to better delineate the relationship between AAC intervention and speech production across a wider range of participants and AAC interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
163
0
27

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 364 publications
(194 citation statements)
references
References 38 publications
4
163
0
27
Order By: Relevance
“…Studies [19][20][21][22][23] have shown that the presence of language difficulties and cognitive deficits is a relevant condition to indicate the use of systems and symbols from Augmentative and Alternative Communication (AAC) for this population, which includes, temporarily or permanently, individuals with DS. In other words, depending on the individual's profile of communication difficulties, the use of AAC could be a tool for language support or an alternative resource for language expression.…”
Section: This Research Was Approved By the Ethicsmentioning
confidence: 99%
“…Studies [19][20][21][22][23] have shown that the presence of language difficulties and cognitive deficits is a relevant condition to indicate the use of systems and symbols from Augmentative and Alternative Communication (AAC) for this population, which includes, temporarily or permanently, individuals with DS. In other words, depending on the individual's profile of communication difficulties, the use of AAC could be a tool for language support or an alternative resource for language expression.…”
Section: This Research Was Approved By the Ethicsmentioning
confidence: 99%
“…O uso da CSA tem como objetivo o desenvolvimento da competência comunicativa do seu usuário, e é possível que tenha efeitos positivos inclusive para a produção oral (Millar et al, 2006).…”
Section: I In Nt Tr Ro Od Du Uç çã ãO Ounclassified
“…São poucos os estudos na literatura que abordam o uso da CSA especificamente em grupos de indivíduos com SD, embora sejam referidos claramente como candidatos ao seu uso, muitas vezes juntamente com outras populações (déficits cognitivos, outras síndromes, autistas) (Beukelman e Mirenda, 1998;Millar et al, 2006;Roberts et al, 2007a;Rudd et al, 2007).…”
Section: I In Nt Tr Ro Od Du Uç çã ãO Ounclassified
See 2 more Smart Citations